Hypoxia, MTOR and autophagy: Converging on senescence or quiescence - Blagosklonny, Mikhail V. (Landes Bioscience, 2013)
Although hypoxia can cause cell cycle arrest, it may simultaneously suppress a conversion from this arrest to senescence. Furthermore, hypoxia can suppress senescence caused by diverse stimuli, maintaining reversible quiescence instead. Hypoxia activates autophagy and inhibits MTOR, thus also activating autophagy. What is the relationship between autophagy and cellular senescence? Also, can inhibition of MTOR and stimulation of autophagy explain the gerosuppressive effects of hypoxia?